Dosing high-risk calves at processing with Lactipro decreases the number of calves treated for bovine respiratory disease - Miller, K.A.; Van Bibber-Krueger, C.L.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Bovine respiratory disease is the leading cause of cattle mortalities in U.S. feedlots. In addition to costs associated with death loss and medical treatments, cattle affected by respiratory disease typically have suboptimal performance. Lightweight calves coming into the feedlot are at high risk for respiratory disease due to the stress associated with weaning, transportation, feed and water deprivation, commingling, castration, and other factors. Calves often have no experience eating from feed bunks and may be unfamiliar with the types of feeds used in feedlots. At the same time, the cattle are susceptible to acidosis due to the concentrate-based diets that are fed, which also can have unfavorable effects on feed intake and performance. Moreover, symptoms of acute acidosis, which include poor appetite, increased respiration rate, lethargy, depression, loss of muscle tone, nasal and ocular discharge, and diarrhea, can be difficult to distinguish from clinical symptoms of respiratory disease. Therapies designed to address respiratory disease are generally ineffective for treating acidosis, inevitably leading to the perception that antibiotic treatments have only limited efficacy. Moreover, acidosis can increase susceptibility of cattle to respiratory disease. Acidosis is most logically dealt with through preventive measures. We hypothesized that Lactipro (MS Biotec; Wamego, KS), a source of the lactate-utilizing bacterium Megasphaera elsdenii, could decrease the incidence of feedlot acidosis in newly arrived feedlot calves. By preventing acidosis, we speculated that clinical symptoms similar to those associated with respiratory disease would be less prevalent, thus decreasing the number of animals inappropriately diagnosed and treated for respiratory disease. Our objective was to determine if dosing cattle with Lactipro at processing would decrease morbidity and mortality in lightweight calves after arrival at the feedlot.
Keywords: Beef; Lactipro; Bovine Respiratory Disease; Performance